Mesonia hitae sp. nov., isolated from the seawater of the South Atlantic Ocean. Issue 8 (17th August 2021) - Zhou, Ying; Gao, Xiujun; Xu, Jingjing; Li, Guizhen; Ma, Rui; Yan, Peisheng; Dong, Chunming; Shao, Zongze
Abstract : A Gram-negative, non-motile, non-spore-forming, aerobic and short rod-shaped bacterial strain R32 T, was isolated from seawater of the South Atlantic Ocean. Strain R32 T grew at 10–40 °C (optimum 28 °C), at pH 6.0–8.0 (optimum 7.0), and in the presence of 3–8 % NaCl (w/v) (optimum 5 %). Cells were oxidase- and catalase-positive. The 16S rRNA gene sequence of strain R32 T shared the highest similarities with Mesonia oceanica (98.3 %), followed by Salegentibacter salarius (93.0 %), Salegentibacter mishustinae (92.8 %), Salegentibacter salegens (92.5 %) and Mesonia maritima (92.4 %). The dominant fatty acids were iso-C15 : 0 (32.7 %) and iso-C17 : 0 3-OH (21.1 %). Menaquinone-6 (MK-6) was detected as the sole respiratory quinone. The polar lipids found were phosphatidylethanolamine, three aminolipids and three unidentified lipids. The DNA G+C content was 35.0 mol%. The ANI value and dDDH value between strain R32 T and the Salegentibacter and Mesonia species were 70.5–85.8 % and 18.7–30.5 %, respectively. Based on the results of the polyphasic characterization, strain R32 T is considered to represent a novel species of the genus Mesonia, for which the name Mesonia hitae sp. nov. is proposed. The type strain is R32 T (=MCCC 1A09780 T =KCTC 72004 T ).